THE EFFECT OF PHET-ASSISTED JIGSAW TYPE COOPERATIVE LEARNING MODEL ON STUDENTS' LEARNING OUTCOMES INPRIVATE HIGH SCHOOL GRADE XI WAVE MATERIALGAJAH MADA MEDAN 2022/2023 Academic Year - Budi (Jurnal Edukasi dan Pembelajaran STEM, 2025)
The purpose of this study is to determine the broad impact of the use of the Jigsaw cooperative mastery model assisted by PheT on the results of students' attention recognition on the greatness of XI SMA Gajah Mada Medan Academic Year 2022/2023. The form of this research is a quasi-experimental research. The population of this study was all students of class XI MIPA at SMA Swasta Gajah Mada Medan Academic Year 2022/2023. The sample in this study was taken using cluster random sampling, namely the experimental class of 30 students implemented to the Jigsaw cooperative mastery model assisted by PhET and the control class of 28 students implemented to the DI version. This observation tool uses an essay test with ten proven questions used in this study. The average pre-test score of the experimental class is 32.89 with a normal deviation of 2.99 and the average post-test score is 84.33 with a normal deviation of 2.72. These figures are based entirely on research findings. The suggested pretest ratings and desired deviations for the manipulation style were 35.44 and 3.82, respectively , and the intended posttest ratings were 71.33 and 5.93. Lcount Ltable was accepted for each instruction with a daily distribution, even as Fcount obtained Ftable for homogeneous elegance. The results of the statistical test (t-party test ) and dk 56 found that the initial abilities of the 2 lessons were the same because tcount < ttable, or -0.84 1.94, is true. Furthermore, exclusive treatment has been applied to 2 lessons and towards the end of the lesson a publication test was given. From the results of the statistical test of the fact (one-celebration t check) it was obtained tcount > ttable, namely 2.41 > 1.94, this indicates that there is a possibility of a Jigsaw type cooperative learning model that has a large influence with the help of PhET on student learning outcomes. resulting in excessive magnificence of Gajah Mada's personal XI questions, faculty of 2022/2023 academic year .